Global Banks and Synthetic Funding: The Benefits of Foreign Relatives - Fernando Eguren-Martin; Matias Ossandon Busch; Dennis Reinhardt (Journal of Money, Credit and Banking, 2023)
This paper examines the effect of dislocations in foreign currency (FX) swap markets (“CIP deviations”) on bank lending. Using data from UK banks we show that when the cost of obtaining swap-based funds in a particular foreign currency increases, banks reduce the supply of cross-border credit in that currency. This effect is increasing in the degree of banks' reliance on swap-based FX funding. Access to foreign relatives matters as banks employ internal capital markets to shield their cross-border FX lending supply from the described channel. Partial substitution occurs from banks outside the UK not affected by changes in synthetic funding costs.
Keywords: 330; cross-border bank lending; covered interest rate parity deviations; FX swaps; internal capital markets